Rancang Bangun Mesin Penggiling Sekam Padi Menjadi Bahan Pakan Ternak (Dedak) - Arif Baidilah; Kardiman Kardiman; Farradina Choria Suci (Politeknik Negeri Padang, 2021)
In the development of technology and industry, a lot of tools are made to make it easier to do work. In the farming sector, a lot of tools are needed to facilitate development in the farming sector. One of the tools needed is a machine to make animal feed. One of the ingredients for making animal feed is bran, bran produced from the process of milling rice husks. To produce bran, a tool that can crush rice husks into the form of flour is designed to make animal feed suitable, as well as make the shape of a portable grinding machine. In this design, data collection steps were carried out with literature studies and after that carried out experiments on the manufacture of rice husk grinding machines. In conducting the experiment, the concept of design, design, calculation, manufacture and testing of grinding machines was also carried out. The result of this design is the design of a grinding machine and a grinding machine that can smooth rice husks into flour and portable forms. The specifications of the rice husk grinding machine are a frame with a length of 580 mm, a width of 380 mm and a height of 995 mm. Drive source 7 HP petrol motor with belt pulley transmission. The speed of the grinding blade shaft can be changed by replacing the pulley on the driving motor so that it can determine the fineness of the bran and the speed of the grinding. As well as the filter on the milling section can be replaced in order to adjust to the required level of fineness.